2022
DOI: 10.37891/kpej.v5i1.230
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Sciences Learning Media Based on Website and Integrated with Youtube Videos

Abstract: There are three types of learning styles, to meet the learning styles of students, both visual and auditory types, there needs to be an innovation of supportive and appropriate learning media. In addition, the learning media can also be one of the supporting media in the implementation of online learning. Therefore, a research was conducted that aims to produce online-based learning media that is integrated with video and audio. The research method used is Research and Development (R&D) with a 3D model con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In general, the assessment results from material experts, media experts, and students showed that the media is in very good categories, indicating that the website is a highly effective learning medium. Other researchers have also developed website-based learning media to improve student learning outcomes, such as the website media developed to support learning in the fields of mathematics, physics, chemistry, language, and design (Arifin & Nugroho, 2023;Manggopa, Manoppo, Togas, Mewengkang, & Batmetan, 2019;Purba, Riris, & Muchtar, 2021;Rukun & Irfan, 2020;Suartini, Sukandar, Zadi, Fikadinda, & Maulana, 2022;Swandi et al, 2022). The cited studies suggest that website-based learning media is an effective tool for improving student learning outcomes.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 99%
“…In general, the assessment results from material experts, media experts, and students showed that the media is in very good categories, indicating that the website is a highly effective learning medium. Other researchers have also developed website-based learning media to improve student learning outcomes, such as the website media developed to support learning in the fields of mathematics, physics, chemistry, language, and design (Arifin & Nugroho, 2023;Manggopa, Manoppo, Togas, Mewengkang, & Batmetan, 2019;Purba, Riris, & Muchtar, 2021;Rukun & Irfan, 2020;Suartini, Sukandar, Zadi, Fikadinda, & Maulana, 2022;Swandi et al, 2022). The cited studies suggest that website-based learning media is an effective tool for improving student learning outcomes.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 99%
“…Video is a combination of moving images, audio, video, animation, and sound which are arranged sequentially to form a flow containing messages with a specific purpose (Kurniawati et al, 2021;Yunnita, 2021). The advantage of using video as a learning medium is that the message conveyed is easier to understand, understand, and stick in memory (Swandi et al, 2022). The steps in creating video content are writing narrative scripts which are then adapted to the visuals and adding interactive elements such as interactive questions (Kestin, 2022).…”
Section: Csermentioning
confidence: 99%